INTEGRATING INDONESIA’S BORDER CONTROL MANAGEMENT SYSTEM: AN ANSWER TO EVER-EVOLVING TRANSNATIONAL ORGANIZED CRIME - Dewanto, Rafi Navynanda Kusuma; Al-Dzikri, Ilham Akbar Dzaky; Bayunillah, Muhammad Okahadiwan; Jannah, Rahmawati Nurul (Polteknik Imigrasi, 2025)
This article examines the critical need for an integrated border control management system in Indonesia, addressing the challenges posed by the country's vast archipelagic geography and the evolving threats of transnational organized crime. It analyzes the current fragmented state of Indonesia's border management, spread across multiple agencies including immigration, customs, maritime security, and border patrol. The study highlights the inadequacies of this system in combating sophisticated criminal networks that exploit jurisdictional gaps and information silos. Drawing on comparative analyses of integrated border management systems in countries such as the United States, Australia, and Singapore, as well as regional models like the European Union, the article proposes potential solutions tailored to Indonesia's unique context. Two primary approaches are discussed: the creation of a new overarching agency consolidating key border management functions, and the establishment of a high-level inter-agency coordination committee. The article emphasizes critical elements for successful integration, including advanced technology deployment, risk-based management approaches, comprehensive training programs, legal reforms, enhanced regional cooperation, and public-private partnerships. It argues that while the path to integration presents significant challenges, including institutional resistance and financial constraints, the benefits of an integrated system far outweigh the costs. The study concludes that implementing an integrated border management system is crucial for enhancing Indonesia's national security, contributing to regional stability, and positioning the country as a leader in innovative border management practices in Southeast Asia. This research contributes to the ongoing dialogue on enhancing national and regional security in the face of complex, transnational threats, offering insights relevant not only to Indonesia but to other nations grappling with similar border management challenges.